2012
DOI: 10.3945/an.112.001990
|View full text |Cite
|
Sign up to set email alerts
|

Orange Juice Limits Postprandial Fat Oxidation after Breakfast in Normal-Weight Adolescents and Adults

Abstract: Caloric beverages may promote weight gain by simultaneously increasing total energy intake and limiting fat oxidation. During moderate intensity exercise, caloric beverage intake depresses fat oxidation by 25% or more. This randomized crossover study describes the impact of having a caloric beverage with a typical meal on fat oxidation under resting conditions. On 2 separate days, healthy normal-weight adolescents (n = 7) and adults (n = 10) consumed the same breakfast with either orange juice or drinking wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Saliva insulin, which varies with plasma insulin in healthy children and adults [57], was monitored instead of plasma insulin to avoid participant drop-out related to weekly blood sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Saliva insulin, which varies with plasma insulin in healthy children and adults [57], was monitored instead of plasma insulin to avoid participant drop-out related to weekly blood sampling.…”
Section: Methodsmentioning
confidence: 99%
“…The primary dependent variable, upon which the study is powered, is lipid oxidation. Power analyses demonstrated that 15 subjects provided greater than 90% power to detect a protein effect of 2 g on lipid oxidation [5] and a beverage effect of 5 g on lipid oxidation [11] given a within-subject SD of 2 g at p = 0.05. Secondary dependent variables included energy expenditure, DIT and protein and carbohydrate oxidation.…”
Section: Calculations and Statistical Analysismentioning
confidence: 98%
“…In addition to increasing energy intake, SSBs may significantly affect postprandial fat oxidation. Stookey et al recently reported that the addition of orange juice with a standard breakfast meal decreased fat oxidation compared to the same meal coupled with water [11]. This acute effect on net fat oxidation leads to preferential increases in visceral adipose tissue when consumed daily over long periods [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoids and flavonoids, due to their antioxidant properties and nutritional benefits, have been some of the most studied dietary and therapeutic components in the dietetics and preventive medicine areas, yielding hundreds of publications and reviews [36,39,41,65,66,[122][123][124][125][126]. Much anecdotal or scientific evidence indicate that some of these components may possess potent antioxidant, anti-inflammatory, antiallergic, hypolipidaemic, vasoprotective, and anticarcinogenic properties [127] and protect against oxidative stress, coronary heart diseases, certain cancers, and other age-related diseases.…”
Section: Dietetics Of Citrus Fruits Pigmentsmentioning
confidence: 99%